On a generalization of Hankel kernel - C. Nasim; B. D. Aggarwala (International Journal of Mathematics and Mathematical Sciences)
We consider an expression involving the Bessel function, the Neumann function and the MacDonald function and discover various combinations of these functions which are Fourier kernels or conjugate Fourier kernels. Also a large number of integration formulae are established involving these kernels.